2014
DOI: 10.1007/s11434-014-0581-2
|View full text |Cite
|
Sign up to set email alerts
|

Research progress in quantifying the mechanical properties of single living cells using atomic force microscopy

Abstract: The advent of atomic force microscopy (AFM) provides a powerful tool for investigating the behaviors of single living cells under near physiological conditions. Besides acquiring the images of cellular ultra-microstructures with nanometer resolution, the most remarkable advances are achieved on the use of AFM indenting technique to quantify the mechanical properties of single living cells. By indenting single living cells with AFM tip, we can obtain the mechanical properties of cells and monitor their dynamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
5
2

Relationship

4
3

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 90 publications
0
11
0
2
Order By: Relevance
“…The conical tips are sharp and they measure the mechanical properties of local areas on the cell surface. In recent years, researchers have used sphere tips to quantify the mechanical properties of the whole living cells [16,35,38,39]. Compared with conical tips, sphere tips have larger contact areas and thus smaller applied pressures, causing that cellular Young's modulus measured with sphere tips is less than that with conical tips [40].…”
Section: Discussionmentioning
confidence: 99%
“…The conical tips are sharp and they measure the mechanical properties of local areas on the cell surface. In recent years, researchers have used sphere tips to quantify the mechanical properties of the whole living cells [16,35,38,39]. Compared with conical tips, sphere tips have larger contact areas and thus smaller applied pressures, causing that cellular Young's modulus measured with sphere tips is less than that with conical tips [40].…”
Section: Discussionmentioning
confidence: 99%
“…After the manipulations are finished, the operator controls AFM tip to another cell. This manualdependent process leads to a very low throughput (the time of handling one cell is often several minutes) [13,62,63]. In practice, in order to obtain statistically significant results, we need to perform experiments on many cells, and this will results in heavy workloads.…”
Section: Discussionmentioning
confidence: 99%
“…The cantilever deflection is constant prior to when the tip contacts the cell, and when the tip begins to indent the cell, the shape of the approach curve becomes bent. In practice, the approach curve is first converted into an indentation curve according to the contact point, and then the Hertz-Sneddon model is applied to calculate the cell Young's modulus [43] . The Hertz-Sneddon model is based on the following expressions [44] :…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%
“…After obtaining the loading force F and the indentation depth δ, the cellular Young's modulus E cell can be calculated according to formulas (6) and (7). It should be noted that the Hertz-Sneddon model is based on a number of assumptions applied to the specimen to be indented, including homogeneity, isotropicity, linear elastic material properties, axisymmetry and infinitesimal deformation of the sample, as well as infinite sample thickness and a smooth sample surface [43,45] . Studies have shown that the Hertz-Sneddon model is appropriate as long as the indentation into the specimen is no more than 10% of the specimen thickness [46] .…”
Section: Wwwchinapharcom LI M Et Almentioning
confidence: 99%